A Web of Watchdogs: Stakeholder Media Networks and Agenda-Setting in Response to Corporate Initiatives - Besiou, Maria; Hunter, Mark Lee; Van Wassenhove, Luk N. (2013)
This article seeks to model the agenda-setting strategies of stakeholders equipped with online and other media in three cases involving protests against multinational corporations (MNCs). Our theoretical objective is to widen agenda-setting theory to a dynamic and nonlinear networked stakeholder context, in which stakeholder-controlled media assume part of the role previously ascribed to mainstream media (MSM). We suggest system dynamics (SD) methodology as a tool to analyse complex stakeholder interactions and the effects of their agendas on other stakeholders. We find that largely similar dynamics of interactions occur among stakeholders in these cases, and that the costs for managements of maintaining their agendas steadily rises. We conclude that the “web of watchdogs” comprises a powerful reason for managers to engage in responsibility negotiations with their stakeholders.
Keywords: System dynamics; Stakeholder media; Stakeholder; Media; Agenda-setting